Utilisation of Biochar from Kapok Randu (Ceiba pentandra) Branches for Decolourisation of Remazol Red in Water - Alfina D. A. Dasi; Mery Napitupulu; Daud K. Walanda; Sitti Rahmawati (Jurnal Akademika Kimia, 2026)
Synthetic dyes such as remazol red are commonly used in the batik process, but their residual waste is a major contributor to water pollution. These effluents can degrade water quality, damage aquatic ecosystems, and pose health risks to humans. This research aims to reduce these problems by using an adsorption method that utilises kapok randu branch as an adsorbent for remazol red dye. Kapok randu branches were pyrolysed at temperatures of 400 °C, 450 °C, and 500 °C. This study aims to measure the ability of biochar from kapok randu branches to adsorb remazol red dye under varying weight, time, and pH conditions. The results showed the characteristics of kapok randu branches biochar include moisture content of 400 °C, 450 °C and 500 °C biochar of kapok randu branches of 5.56 %, 5.01 % and 4.80 %, respectively. The ash content of the 400 °C, 450 °C, and 500 °C kapok randu branch biochar was 5.68 %, 6.66 %, and 7.24 %, respectively. The maximum weight of kapok randu branch biochar in adsorbing remazol red dye is 25 mg with an adsorption capacity of 0.312 mg/g. The maximum contact time required was 60 minutes with an adsorption capacity of 1.004 mg/g. The maximum pH for the remazol red dye during the adsorption process was at pH 4, with an adsorption capacity of 5.816 mg/g.